(untitled) (Altre Modernità, 2012)
The Hare with Amber Eyes (2010) by Edmund de Waal is a memoir written by “a very textual potter”. Thanks to the inheritance of a collection of tiny Japanese carvings, de Waal leaves on a journey to Paris, Vienna, Odessa, back to his Jewish roots in nineteenth century aesthtecisism and in the tragedy of the Shoah. Drawing parallels between his writing, collecting and the plastic arts of pottery, the author explores the affinities between artefact and word, installation and proposition, collection and archive. The Hare can be read in the context of what R. Wendorf has defined a “literature of collecting,” including critical theory as well as narratives dealing with its practices. Rich in intertextual excursions, de Waal’s autobiographical writing develops a fruitful conversation with W. Benjamin’s 1931 paradigmatic text “Unpacking my Library”. Also P. Levi’s La chiave a stella riverberates in the writer’s awareness of the importance of precision in practices like creating an installation and writing about the past, involving both aesthetic and moral responsabilities. De Waal’s stance about the transitivity between art and writing finally emerges from the very rhetorics of his work which abounds in circular structures like the red alluminium ring which sustains his installation at the V&A Ceramics Galleries and the figure of the chiasmus which organizes his prose writing, linking him yet again to his Jewish cultural origins.